Comparing 11 nutrition-inflammation indices for perioperative management and prognostic evaluation in non-small cell lung cancer patients - Wang, Yuanfang; Zhang, Hui; Li, Fang; Zhang, Zhao; Wang, Jing; Wu, Qiuge (Frontiers in Nutrition, 2025)
BackgroundDespite the establishment of multiple nutrition-inflammation indices, their performances in guiding clinical decision-making have not been systematically compared in patients with non-small cell lung cancer (NSCLC). This study aimed to identify the best nutrition-inflammation index for facilitating perioperative management and prognosis analysis in NSCLC patients.MethodsThis study included NSCLC patients who underwent video-assisted thoracoscopic lobectomy as their primary treatment. Nutrition-inflammation indices were calculated based on blood tests and anthropometric measurements conducted within one week prior to surgery. A total of 11 nutrition-inflammation indices were compared for their performance in predicting perioperative and survival outcomes.ResultsThe cohort consisted of 805 patients, with a mean age of 60.3 years, including 388 females (48.2%) and 417 males (51.8%). Postoperative complications occurred in 152 patients (18.9%). The median follow-up time after surgery was 64.5 months. Most nutrition-inflammation indices demonstrated predictive values for perioperative complications, delayed hospital discharge, and survival outcomes, but with relatively low predictive accuracy. After adjusting for clinicopathological characteristics, most indices were no longer associated with these therapeutic outcomes. Among these indexes, the lymphocyte-to-monocyte ratio showed the best performance in predicting perioperative complications and delayed hospital discharge, while the geriatric nutritional risk index showed the best performance in predicting overall survival and disease-free survival.ConclusionThe current nutrition-inflammation indices demonstrated predictive values for therapeutic outcomes in NSCLC patients, but their utility in clinical practice may be limited due to generally weak independent associations. Future studies should focus on exploring more comprehensive nutrition-inflammation biomarkers for assisting clinical decision-making.